1977
DOI: 10.1007/bf00220349
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the rat pineal gland grafted under the kidney capsule

Abstract: Pineal glands were grafted under the kidney capsule of mature male rats for periods of 20, 40, 60 and 100 days. Each grafted gland was then excised and divided into two halves. One half was processed for conventional electron microscopy and the other was fixed in aldehydes and then incubated in a zinc-iodide-osmium tetroxide mixture at pH 4.4 (A-ZIO-4.4). During the forty days following the operation pinealocytes showed the typical ultrastructural features associated with cells with a high protein and/or pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…To support this observation, more complicated studies have been performed in which pineal glands were transplanted into a variety of sites in pinealectomized rats. These sites included anterior chamber of the eye, third cerebral ventricle, the pineal region (in situ transplantation), intrastriatal, renal capsule and thymus [ 280 , 281 , 282 , 283 , 284 , 285 ]. The results indicated that in some cases the pineal gland transplantation did increase the melatonin levels in pinealectomized animals; however, except in the site of anterior chamber of the eye, no melatonin circadian rhythm was detected with the pineal gland transplantation and also the melatonin levels could not match those of the in situ pineal gland produced.…”
Section: Rejuvenation Of Pineal Gland?mentioning
confidence: 99%
“…To support this observation, more complicated studies have been performed in which pineal glands were transplanted into a variety of sites in pinealectomized rats. These sites included anterior chamber of the eye, third cerebral ventricle, the pineal region (in situ transplantation), intrastriatal, renal capsule and thymus [ 280 , 281 , 282 , 283 , 284 , 285 ]. The results indicated that in some cases the pineal gland transplantation did increase the melatonin levels in pinealectomized animals; however, except in the site of anterior chamber of the eye, no melatonin circadian rhythm was detected with the pineal gland transplantation and also the melatonin levels could not match those of the in situ pineal gland produced.…”
Section: Rejuvenation Of Pineal Gland?mentioning
confidence: 99%
“…Moreover, the donor/host origin of blood vessels vascularizing the grafts is expected to influence both the permeability of the blood-brain barrier (BBB) within the grafts (Rosenstein and Brightman 1983;Broadwell et al 1990) and the susceptibility of the graft to rejection by circulating cells of the host immune system (Low et al 2000). Several studies have been reported involving the transplantation of the mammalian pineal gland to various sites (Aguado et al 1977;Lingappa and Zigmond 1987), including the CNS (Brightman et al 1985;Wu et al 1990Wu et al , 1991Wu et al , 1993. However, the majority of these investigations have concentrated on the normal development and differentiation of pinealocytes, the recovery of the functional activity of grafts after pineal transplantation or the re-innervation of grafts and the contribution of various types of afferents to pineal function (Nonaka et al 1990;Wu et al 1990Wu et al , 1993McNulty et al 1991;Zsarnovszki et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The history of pineal transplantation has been reviewed recently by Quay (1987) and will not be repeated here. It is necessary t o note, however, that the mammalian pineal gland has been grafted to a number of different sites including the anterior chamber of the eye (Backstrom et al, 1976(Backstrom et al, , 1977Lingappa and Zigmond, 1987;Wragg et al, 1967); under the renal capsule (Aguado et al, 1977;Gittes and Chu, 1965;Simionescu and Scherzer, 1969); intramuscularly (Gittes and Chu, 1965;Simionescu and Scherzer, 1969); within gonads (testes and ovaries), subcutaneous connective tissue, and thyroid (Simionescu and Scherzer, 1969); in the adrenal (Quay, 1976;Simionescu and Scherzer, 1969); and in the submandibular gland and orbital glands and into interscapular brown fat (Quay, 1976). The majority of these studies have focused on the function of the superior cervical ganglia as the postganglionic sympathetic fibers from the ganglia reinnervate the pineal graft (Backstrom et al, 1976;Wragg et al, 1967), or on transplant vascularization (Klausen et al, 1989).…”
Section: Introductionmentioning
confidence: 99%